2020
DOI: 10.1093/nar/gkaa901
|View full text |Cite
|
Sign up to set email alerts
|

EWS-FLI1 regulates and cooperates with core regulatory circuitry in Ewing sarcoma

Abstract: Core regulatory circuitry (CRC)-dependent transcriptional network is critical for developmental tumors in children and adolescents carrying few gene mutations. However, whether and how CRC contributes to transcription regulation in Ewing sarcoma is unknown. Here, we identify and functionally validate a CRC ‘trio’ constituted by three transcription factors (TFs): KLF15, TCF4 and NKX2-2, in Ewing sarcoma cells. Epigenomic analyses demonstrate that EWS-FLI1, the primary fusion driver for this cancer, directly est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…This model is very plausible as NKX2.2 is a core circuitry complex component and has a proven co-regulatory role in pancreatic cells [ 33 ]. Our findings are further supported by a recent report showing that EWSFLI1 regulates and cooperates with core regulatory circuitry (CRC)-dependent transcriptional networks in ES [ 62 ]. Shi et al in their recent work indicated that NKX2.2, upon upregulation, binds to its own promoter, super-enhancers, and the promoters of KLF15 and TCF4 to form an interconnected autoregulatory loop [ 62 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This model is very plausible as NKX2.2 is a core circuitry complex component and has a proven co-regulatory role in pancreatic cells [ 33 ]. Our findings are further supported by a recent report showing that EWSFLI1 regulates and cooperates with core regulatory circuitry (CRC)-dependent transcriptional networks in ES [ 62 ]. Shi et al in their recent work indicated that NKX2.2, upon upregulation, binds to its own promoter, super-enhancers, and the promoters of KLF15 and TCF4 to form an interconnected autoregulatory loop [ 62 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are further supported by a recent report showing that EWSFLI1 regulates and cooperates with core regulatory circuitry (CRC)-dependent transcriptional networks in ES [ 62 ]. Shi et al in their recent work indicated that NKX2.2, upon upregulation, binds to its own promoter, super-enhancers, and the promoters of KLF15 and TCF4 to form an interconnected autoregulatory loop [ 62 ]. Our work confirms for the first time that NKX2.2 occupies proximal sites on the STEAP1 promoter, known to be regulated by EWSFLI1.…”
Section: Discussionsupporting
confidence: 88%
“…NR0B1 have been associated with the tumor phenotype mediated by EWS/FLI chimera in cell lines [ 38 ]. NKX2–2, a homeodomain transcription factor involved in neuroendocrine/glial differentiation and a downstream target of EWSR1-FLI1, has been reported as an immunohistochemical marker for Ewing sarcoma [ 39 ]. We identified both NR0B1 and NKX2-2 as MRs in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang was recently the first to study SE-associated CRC transcriptional control in lung adenocarcinoma: master TFs ELF3 , EHF , and TGIF1 were found to co-occupy the SE region and promote each other’s expression through the formation of CRC, which induces the malignant progression of lung adenocarcinoma [ 109 ]. Similarly, in Ewing sarcoma, KLF15 , TCF4 , and NKX2–2 have been identified as the master TFs containing both EWS-FLI1 binding motif and SE peaks [ 110 ]. Importantly, these three CRC TFs co-regulate the PI3K/AKT and MAPK signaling pathways to promote the aggressiveness of Ewing sarcoma [ 110 ].…”
Section: Structures and Functions Of Sesmentioning
confidence: 99%
“…Similarly, in Ewing sarcoma, KLF15 , TCF4 , and NKX2–2 have been identified as the master TFs containing both EWS-FLI1 binding motif and SE peaks [ 110 ]. Importantly, these three CRC TFs co-regulate the PI3K/AKT and MAPK signaling pathways to promote the aggressiveness of Ewing sarcoma [ 110 ].…”
Section: Structures and Functions Of Sesmentioning
confidence: 99%